Phenomena that were not included in filtration modelling - Dąbrowski, Wojciech (Instal, 2023)
The method of carrying out and the results of experiments are described, showing a significant impact on depth filtration of phenomena such as the thickening of the filter bed over time and the compressibility of post-coagulation sediments, as well as, probably at the end of filtration, sediment suffusion of a different character than was expected before. These phenomena are co-responsible, together with others, for the lack of success in using methods of mathematical modelling of the filtration process.